2022
DOI: 10.3126/banko.v32i1.45476
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for involving community forest managers in effective forest fire management in Nepal

Abstract: Each year forest fire causes enormous damage to Nepal's forest ecosystems and landscape. For an active community involvement at the landscape level, policymakers must take the interests of local forest managers into account to increase social acceptability. This research explores the perception of community forest managers, who are constantly managing forests at the grassroots level, to understand the relationship between their priorities, needs, and attitudes toward forest fire management. Eighty–eight key in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This has been regulated in the policy of prohibiting forest fires, which also regulates the obligation of the community and the private sector to be involved in forest fires management consciously (62). In other countries, such as Nepal, it is also shown that community involvement is the most important activity in forest fires management (63). How important these community actors are, they are the key to forest survival through the integration of local wisdom, conservation values, and sustainable livelihoods (64), especially at the preventive stage (65).…”
Section: Discussionmentioning
confidence: 99%
“…This has been regulated in the policy of prohibiting forest fires, which also regulates the obligation of the community and the private sector to be involved in forest fires management consciously (62). In other countries, such as Nepal, it is also shown that community involvement is the most important activity in forest fires management (63). How important these community actors are, they are the key to forest survival through the integration of local wisdom, conservation values, and sustainable livelihoods (64), especially at the preventive stage (65).…”
Section: Discussionmentioning
confidence: 99%
“…Given that fires in Nepal are managed by communities rather than a centralized agency, with no nationallevel policy or plan for forest fire management, an increase in forest fires poses a significant challenge to the effectiveness of community management (Sapkota et al 2015). While the Nepal Army often mobilized if a fire threatens settlements, there is no dedicated team to suppress wildland fires in Nepal, and local community members are often trained as firefighting volunteer groups at the district or village level (Matin et al 2017;Parajuli et al 2022). Assuming that there is no significant change in these policies at a national level, community-based fire management capacity will be critical to control and, when needed, to suppress wildfires in Nepal to ensure successful and sustainable forest management (Parajuli et al 2022), and these ad hoc groups may benefit from easily derived prediction metrics and a reference of early warming.…”
Section: Discussionmentioning
confidence: 99%
“…While the Nepal Army often mobilized if a fire threatens settlements, there is no dedicated team to suppress wildland fires in Nepal, and local community members are often trained as firefighting volunteer groups at the district or village level (Matin et al 2017;Parajuli et al 2022). Assuming that there is no significant change in these policies at a national level, community-based fire management capacity will be critical to control and, when needed, to suppress wildfires in Nepal to ensure successful and sustainable forest management (Parajuli et al 2022), and these ad hoc groups may benefit from easily derived prediction metrics and a reference of early warming. Qadir et al (2021) developed a fire forecast model for Nepal that used multiple sources of satellite data.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) argued that distance to and settlement might have a lower impact on risk in specific locations, an effect largely driven by human behaviour and habits. Parajuli et al, (2022) state that most forest fires in the Terai region are due to human negligence and lack of awareness, indicating that human population density during critical periods may be the underlying driver. In this light, selecting the variables influencing forest fire and considering them in the right context is critically important when conducting multicriteria analysis.…”
Section: Discussionmentioning
confidence: 99%